Teori Resiprocal Tolerance dalam Harmonisasi Mayoritas-Minoritas di Kepulauan Mentawai Sumatera Barat - Muhammad Taufiq (Institut PTIQ Jakarta, 2017)
The majority and minority of religious people in Indonesia has always been a hot conversation, especially in the context of reli- gious social relations. Mentawai, geographically, located in the prov- ince of West Sumatra has a uniqueness, where the majority people of Padang is Minang. Minewhile, Mentawai people is not including Minang people. On the other hand, West Sumatra people embrace Materilinial descent system while Mentawai people do not embrace it. This is because the Mentawai people do not embrace Islam. Al- though Mentawai Muslims are in a minority position compared to other faiths, they are able to live a harmonious life and even respect each other’s traditions, customs, and rituals of particular religions and communities. In various regions of Indonesia and, even, in the world today there is disharmonization among religious people, while in Mentawai, all forms of destructive relationship can be overcome. This paper is intended to see the harmonic relation with the theory of resiprocal tolerance.